A review of the literature on vocational training interventions with individuals with autism spectrum disorder. (18th May 2021) - Campanaro, Alexandra M.; Vladescu, Jason C.; Manente, Christopher J.; Deshais, Meghan A.; DeBar, Ruth M.
Abstract: Due to the low employment rates of adults with autism spectrum disorder, it is important to identify efficient and effective methods to teach these individuals vocational skills. The purpose of the current literature review was to expand on the previous reviews, to identify all studies regardless of participant age that taught vocational skills. A total of 50 articles containing 53 experiments were retained and included in the final review. The most commonly used interventions either alone or as part of packaged intervention included video modeling, behavioral skills training, feedback, and video prompting. Articles were coded according to various participant characteristics, settings, intervention methodologies and outcomes. Overall results and implications for future research are discussed.